Digitalize Training Administration Application to Support Aviation Polytechnic towards Smart Vocational Training Centre - Ayub Wimatra; Hadi Prayitno; Sukarwoto; Ahnis Zulkarnain (GoAcademica Research & Publishing, 2023)
This research aims to develop a